2018
DOI: 10.1016/j.ijscr.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Nodular fasciitis mimicking a soft tissue sarcoma – A case report

Abstract: HighlightsNodular Fasciitis, also known as infiltrative or pseudosarcomatous fasciitis, is a benign soft tissue tumour of fibroblastic/myofibroblastic differentiation.Magnetic Resonance Imaging was done and showed an irregular mass in the right axilla in the muscular- subcutaneous plane measuring 10.8 × 8.8 × 12 cm.Positive staining with alpha smooth muscle actin(SMA) is a feature of nodular fasciitis suggesting a myofibroblastic differentiation and less possibility of a sarcoma.Treatment options include, obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…On MRI, this condition usually demonstrates homogenous hypo-isointensity of signal on T1-W scans and heterogeneous hyperintensity on T2-W, with variable grade of contrast enhancement appreciable on the border [2] . However, the lesion can sometimes appear hyperintense even in T1-W sequences [25] .…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, this condition usually demonstrates homogenous hypo-isointensity of signal on T1-W scans and heterogeneous hyperintensity on T2-W, with variable grade of contrast enhancement appreciable on the border [2] . However, the lesion can sometimes appear hyperintense even in T1-W sequences [25] .…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Konwaler [4] in 1955 as subcutaneous pseudosarcomatous fibromatosis. The mass is usually less than 4 cm in diameter [3] and 71% are smaller than 2 cm [5]. Nodular fasciitis may occur anywhere on the body, but most commonly affects the forearm (27–29%) [2].…”
Section: Discussionmentioning
confidence: 99%
“…It sometimes shows spontaneous regression [6] and recurrence is rare, even after incomplete excision [2], with no reports of malignant transformation. These lesions may show atypia and mitoses, making nodular fasciitis difficult to distinguish from sarcoma [5,[7], [8], [9]]. In fact, Plaza et al [10] reported that two thirds of their cases were misdiagnosed as sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Bernstein et al reported that lesions of NF rarely exceed 4 cm and 71% were smaller than 2 cm in their series comprising 134 cases [8]. Lesions may be found anywhere on the body but most commonly on the forearm (27-29%), back or chest wall (15-18%), and upper arm (12%) [3]. Intravascular fasciitis and cranial fasciitis are known subtypes of NF [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NF lesions are usually less than 3-4 cm in diameter. Due to its rapidly growing nature, a precise clinical diagnosis is difficult, and the condition is frequently misdiagnosed as an aggressive or malignant tumor [3]. Recently, USP6 fluorescence in situ hybridization (FISH) analysis has been considered an important diagnostic tool for NF in conjunction with clinical and cytological findings [4].…”
Section: Introductionmentioning
confidence: 99%